2010
DOI: 10.1074/jbc.m110.120956
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Residues in the Extracellular Domain of Thrombopoietin Receptor Involved in the Binding of Thrombopoietin and a Nuclear Distribution Protein (Human NUDC)

Abstract: Thrombopoietin (TPO) and its receptor (Mpl) have long been associated with megakaryocyte proliferation, differentiation, and platelet formation. However, studies have also shown that the extracellular domain of Mpl (Mpl-EC) interacts with human (h) NUDC, a protein previously characterized as a human homolog of a fungal nuclear migration protein. This study was undertaken to further delineate the putative binding domain on the Mpl receptor. Using the yeast two-hybrid system assay and co-immunoprecipitation, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…The 4 somatic mutations we identified were affecting the extracellular ligand binding domain of the MPL, 30,31 whereas the 2 germline mutations affected the membrane proximal extracellular domain which appears to play a role in negative regulation of receptor activation. We initially hypothesized that the mutations might affect the affinity to TPO, however, the luciferase assay we performed in g2A cells showed that all identified mutants activated STAT5-induced transcription in the absence of stimulation with TPO.…”
Section: Discussionmentioning
confidence: 99%
“…The 4 somatic mutations we identified were affecting the extracellular ligand binding domain of the MPL, 30,31 whereas the 2 germline mutations affected the membrane proximal extracellular domain which appears to play a role in negative regulation of receptor activation. We initially hypothesized that the mutations might affect the affinity to TPO, however, the luciferase assay we performed in g2A cells showed that all identified mutants activated STAT5-induced transcription in the absence of stimulation with TPO.…”
Section: Discussionmentioning
confidence: 99%
“…This potentially includes both Hsp90-dependent pathway 40 and direct chaperone activity 40,44 . Finally, there is a set of papers exploring the hypothesis that NudC is a secreted protein which functions by binding to the extracellular domain of the thrombopoietin receptor 4550 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a soluble extracellular domain where all the 4 Asn sites were mutated to Gln failed to exert inhibition ( Figure 5B). However, CALR del52 mutant could still induce activation of the Tpo-binding-deficient TpoR mutant (D261A/L265A) 36 ( Figure 5C). Altogether these results show that activation of TpoR by CALR mutants is dependent on TpoR N-glycosylation sites, but independent of the Tpo binding site.…”
Section: 3435mentioning
confidence: 99%